Jīwana kathā Khālase dī mātā Sāhiba Kaura : Srī Gurū Gobinda Siṅgha jī mahārāja de tīsare mahila - Salāra, Harī Siṅgha, 1908- (Nirañjana Siṅgha, 1978)
On the life of Sāhiba Kaura, 1681-1747, wife of Gobind Singh, 10th Guru of the Sikhs.